2014
DOI: 10.1038/emm.2014.65
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress enhances progression of periodontitis via α1-adrenergic signaling: a potential target for periodontal disease therapy

Abstract: This study assessed the roles of chronic stress (CS) in the stimulation of the sympathetic nervous system and explored the underlying mechanisms of periodontitis. Using an animal model of periodontitis and CS, the expression of tyrosine hydroxylase (TH) and the protein levels of the α1-adrenergic receptor (α1-AR) and β2-adrenergic receptor (β2-AR) were assessed. Furthermore, human periodontal ligament fibroblasts (HPDLFs) were stimulated with lipopolysaccharide (LPS) to mimic the process of inflammation. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
(30 reference statements)
1
23
0
1
Order By: Relevance
“…TRAP is a resorptive enzyme found in the ruffled border of the osteoclast membrane and is considered a specific marker of osteoclast differentiation . The suppression of osteoclastic formation is reported to be a result of the pharmacological blockade of α1‐AR and β2‐AR on the surfaces of osteoblasts, which prevents their binding to adrenergic neurotransmitters and reduces the expression of RANKL, the main inducer of osteoclastogenesis and osteoclastic activity . Similar effects were found by Okada et al and Rodrigues et al, who reported a reduction in the number of osteoclasts and the prevention of alveolar bone loss in rats with experimental periodontitis after the blockade of β‐receptors by the intraperitoneal or oral administration of propranolol.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…TRAP is a resorptive enzyme found in the ruffled border of the osteoclast membrane and is considered a specific marker of osteoclast differentiation . The suppression of osteoclastic formation is reported to be a result of the pharmacological blockade of α1‐AR and β2‐AR on the surfaces of osteoblasts, which prevents their binding to adrenergic neurotransmitters and reduces the expression of RANKL, the main inducer of osteoclastogenesis and osteoclastic activity . Similar effects were found by Okada et al and Rodrigues et al, who reported a reduction in the number of osteoclasts and the prevention of alveolar bone loss in rats with experimental periodontitis after the blockade of β‐receptors by the intraperitoneal or oral administration of propranolol.…”
Section: Discussionsupporting
confidence: 65%
“…Similar effects were found by Okada et al and Rodrigues et al, who reported a reduction in the number of osteoclasts and the prevention of alveolar bone loss in rats with experimental periodontitis after the blockade of β‐receptors by the intraperitoneal or oral administration of propranolol. In addition, these drugs have been shown to reduce the levels of IL‐1β (Ph and Pr), IL‐6 (Ph), IL‐8 (Ph), TNF‐α (Pr), and RANKL (Pr) in gingival tissues and increase the expression of OPG (Pr) . It is noteworthy, however, that the beneficial effects observed at these dosages on osteoclastogenesis in this study were not enough to produce a significant improvement in periodontal repair or the formation and resorption of bone, cementum, and dentin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, because it is an alteration with systemic triggers for the individual over a prolonged period of time, it is suggested that immunological changes (exacerbation in the expression of cytokines), endocrine, and behavioral disorders (poor oral hygiene, smoking, and other deleterious habits) predispose to the susceptibility to both diseases …”
Section: Discussionmentioning
confidence: 99%
“…For Lu et al [60], this rapid evolution is because of the stimulation of the stress-induced ANS stimulation, which results in the release of neurotransmitters (catecholamine neurotransmitter, epinephrine). These neurotransmitters are capable of binding to a1-adrenergic (a1-AR) receptors present on the surface of periodontal cells, thus decreasing their biological activity and causing a massive release of inflammatory factors [60].…”
Section: Blood Flow To the Gingivamentioning
confidence: 99%